2019
DOI: 10.1038/s42255-019-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic dopamine signalling regulates brown fat thermogenesis

Abstract: Dopamine signaling is a crucial part of the brain reward system and can affect feeding behavior. Dopamine receptors are also expressed in the hypothalamus, which is known to control energy metabolism in peripheral tissues. Here we show that pharmacological or chemogenetic stimulation of dopamine receptor 2 (D2R) expressing cells in the lateral hypothalamic area (LHA) and the zona incerta (ZI) decreases body weight and stimulates brown fat activity in rodents in a feedingindependent manner. LHA/ZI D2R stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 99 publications
3
54
2
Order By: Relevance
“…The lack of effects of the D2-agonist on iBAT thermogenesis shown in our study seemingly contradicts a recent study, where hypothalamic D2-agonist administration decreased body weight and stimulated iBAT activity in rodents 55 . However, in this study the effects of the D2-agonist were demonstrated to be mediated via centrally initiated activation of the sympathetic nervous system.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of effects of the D2-agonist on iBAT thermogenesis shown in our study seemingly contradicts a recent study, where hypothalamic D2-agonist administration decreased body weight and stimulated iBAT activity in rodents 55 . However, in this study the effects of the D2-agonist were demonstrated to be mediated via centrally initiated activation of the sympathetic nervous system.…”
Section: Discussioncontrasting
confidence: 99%
“…Such adaptations to caloric restriction presumably arise to promote physical activity required to forage for food to obtain needed calories (26), making them potential therapeutic targets for reducing hyperactivity in AN. Dopamine also contributes to thermoregulation (95)(96)(97), which is altered in AN (6,98) and ABA (94,99). Hypothermia arising from weight loss may also induce changes in dopamine.…”
Section: Dopamine and An Vulnerabilitymentioning
confidence: 99%
“…The dopamine receptor 2 on GABAergic neurons in the LHA and zona incerta appears to be able to upregulate Ucp1, BAT thermogenesis, and energy expenditure in mice. This pathway is dependent on orexin signaling (117). The fact that dopamine plays a role in the orexigenic thermogenesis was reported before, when ablating the dopamine neurons resulted in abolishment of the orexigenic increase in body temperature (98).…”
Section: Neuroendocrine Pathways Involved In Orexigenic Thermoregulationmentioning
confidence: 61%